Assessment of depression in aging contexts: general considerations when working with older adults - Gonçalves, Daniela C. (2009)
Popular assertions portray depression as an inevitable outcome of aging, a widespread image embraced by many health professionals. Although epidemiological data contradict the prevalent image that depressive syndromes increase with age, the prognosis becomes more negative as one grows older. An early thorough assessment is vital to identify depressive symptoms in older adults, thus promoting the development of tailored interventions and improved recovery rates. The main problems associated with the assessment of depressive symptoms in older adults include a lack of knowledge about changes in the pattern of symptoms, the inadequacy of techniques developed for other age cohorts, the misuse of psychometric instruments, and deficits in additional areas of assessment. The underlying goal of this article is to analyze the obstacles to a successful assessment of depression symptoms in older adults, suggesting strategies to overcome them.